PERUBAHAN HASIL BELAJAR PECAHAN DENGAN MODEL COOPERATIVE LEARNING TIPE MAM DAN NHT DI SEKOLAH DASAR - Mahdalena, Dilla; Fitria, Yanti; Zainil, Melva (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This research purpose to compare of the cooperative learning models of the Make A Match type and Numbered Heads Together type to the fractional learning outcomes. This research is an experimental research design with Quasi Exsperimental with pretest-posttest non-equivalent comparison-group design. The sample in this research is class IV1 and IV2. The calculation result of research data used was obtained t-test to = 8,92135 > 1,67469 = table at α level of 0.05. With it can be concluded that there is significant comparison between cooperative learning models Make A Match type and Numbered Heads Together type to the fractional learning outcomes of class IV SD IV Gugus IV Padang Utara.Key Word : MAM, NHT, Fractional Learning Outcomes